EFEKTIVITAS PENGGUNAAN MEDIA KOMIK DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPS: SYSTEMATIC LITERATURE REVIEW - Melisa Andriani; Yuyun Dwi Haryanti; Budi Ferbiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social Studies learning in elementary schools still faces challenges in presenting materials that are often abstract and less engaging for students. One alternative to improve learning quality is the use of comic media, which combines visual elements, text, and narratives to deliver learning content more effectively. This study aims to analyze the characteristics of research and the effectiveness of comic media in improving elementary school students’ learning outcomes in Social Studies through a Systematic Literature Review (SLR) approach. The research method follows the PRISMA 2020 guidelines by identifying, selecting, and analyzing 15 relevant scientific articles. The results indicate that studies on comic media are predominantly conducted using the Research and Development (R&D) method with various development models, including ADDIE, Borg and Gall, Dick and Carey, and Hannafin and Peck. Furthermore, comic media has been proven effective in improving students’ learning outcomes, interest, motivation, and engagement through more attractive and contextual learning presentations. Therefore, comic media can serve as an innovative instructional medium that supports Social Studies learning in elementary schools.